Faktor-Faktor Yang Berhubungan Dengan Kejadian Dismenore Primer Pada Mahasiswi Prodi Keperawatan Angkatan 2020 Di Universitas Indonesia Maju Jakarta Selatan Tahun 2023 - Chika Pramesti Ayunda; Yani Handayani; Saiful Gunardi (Inovasi Kesehatan Global, 2024)
Dysmenorrhea is discomfort during the first or second day of menstruation which is very common. Dysmenorrhea is menstruation that causes pain and is the most common gynecological condition experienced by women according to age level. To find out the factors related to the incidence of primary dysmenorrhea in nursing study students class of 2020 in advanced Indonesian universities in 2023. This research uses quantitative research with a correlative analytical nature, the research design used is cross sectional. The population of this research is 120 female students who experience primary dysmenorrhea, the sample was taken using a random sampling system and the sample of this research totaling 55 female students. it was found that there was a relationship between physical activity and the incidence of primary dysmenorrhea in female students (p=0.011<0.05), there was a relationship between consuming fast food and the incidence of primary dysmenorrhea in female students (p=0.001<0.05) , there is a relationship between exercise and the incidence of primary dysmnorrhea in female students (p=0.017<0.05). There is a relationship between intrinsic and extrinsic factors with the incidence of Primary Dysmenorrhea in female students at the University of Indonesia Maju, South Jakarta.